Literature Review: The Effect of Foot Massage with Lavender Aroma Therapy on Lowering Blood Pressure in Hypertensive Patients - Wahyudin, Dedi; Khasanah, Uswatul; Kamil, Abdurahim (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In an effort to reduce the prevalence of hypertension, hypertension is treated with two types of therapy, namely pharmacological therapy and non-pharmacological therapy (Mulyati et al., 2013). Non-pharmacological therapy is divided into several approaches including: with ingredients (aromatherapy, sinshe), spiritual and supernatural approaches (meditation, yoga, reiki) and with skills (reflection massage) (Wahyuningsih & Astuti, 2013). The purpose of this study was to determine the effect and benefits of foot massage with lavender aromatherapy on reducing blood pressure in patients with hypertension through a literature study. This literature review writing method uses the PICO formula which then selects the appropriate articles through PubMed, proquest, CINAHL and Google Scholar using keywordsfoot massage,Lavender Aromatherapyeffect Of Foot Massage andLavender Aromatherapy, Blood Pressure, Vital signs, MassageTherapy on Blood Pressurepublished in the last ten years (2012–2022 ).of the six relevant articles based on the results of the analysis usingJBI Critical Appraisal Checklistall of them explained the same thing regarding the occurrence of a decrease or change in blood pressure after being given a foot massage intervention with lavender aromatherapy in patients with cardiovascular system disorders due to hypertension. Giving foot massage with lavender aromatherapy is effective in lowering blood pressure in hypertensive patients, therefore it is necessary to have a standard operating procedure (SOP) for therapy in order to get maximum results.